ANALYSIS THE EFFECT OF MARKETING MIX IN PURCHASING DECISION OF GROWING UP MILK (GUM) ON THREE SOCIO-ECONOMIC CLASSES IN MALANG - Sunardi Sunardi; Jabal Tarik Ibrahim; Anas Tain (Socio-Economics/Agribusiness Department, 2016)
The changing of consumer behavior is one of the attractive topic in consumer research. The dynamic of consumer behavior could be part that is caused the shorter life cycle product. Then, proper mapping of consumer’s socio-economic class is important thing to enable manufacturers in providing the best product according to customer expectation. The research aims to obtain an explanation about the effect of marketing mix (product, price, place and promotion) towards purchase decision of Growing Up Milk (GUM) products on three socio-economic classes (lower, middle and upper class) and to discover the differences among those three classes. The study was conducted in Malang using questionnaire and data processed by using Partial Least Squares as an alternative to the Structural Equation Modeling. The results showed that one of the marketing mix whis is product significantly affect purchase decision of GUM across the three classes. Price had significant effect to the purchase decision only at lower and upper class. Furthermore, place and promotion do not significantly affect the purchase decision across all classes. Variation change in endogenous variable (purchase decision) could be explained by exogenous variables (marketing mix), for 64.8% (upper), 48.3% (middle) and 49.9% (lower), respectively. Multi Group Analysis (MGA) showed that there are no significant differences between middle and lower class. A significant differences between upper class and middle class and also between upper class and lower class place on product and price. Upper class tends to purchase GUM due to its quality instead of product design and packaging. Price discount and lower price are not the main factors considered for the upper class.